SANKSI KEBIRI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM PIDANA INDONESIA - Sufyan Ilyas (IAIN Bengkulu, 2018)
This research raises the problem; (1). How is the determination of the sanction of the law that is applied in the Government Regulation Substitute Law (PERPPU) No. 1 of 2016 according to the perspective of Islamic Law, (2). How is the determination of the sanction of the law that is stipulated in the Government Regulation in Lieu of Law (PERPPU) No. 1 of 2016 according to the perspective of Indonesian Criminal Law. This research is a normative legal research with normative juridical approach to trace the legal basis, be it in Islamic law or Criminal Law of Indonesia especially related to sanction of kebiri, method of collecting data using library method, after data collected and then analyzed and interpreted by using deduc- tive method that is to draw general facts to make facts or conclusions gained previously into something special. The results of this study conclude that; (1). In the perspective of Islamic Law, chemical punishment is categorized as a punishment that has a minimum and maximum restriction determined by the judge, so it can be classified as a ta’zir punishment. (2). According to the Indonesian Criminal Law perspective, the determination of the sanction of kebiri aims to safeguard the welfare of the Indonesian people from the pedophile actors, to give a deterrent effect and as a form of responsibility towards the law of the perpetrators.